Dressler-de Winter sign: an independent ECG entity, or a mosaic in the palette of acute coronary syndromes - János Tomcsányi (Cardiologia Hungarica)
Dressler–de Winter sign: an independent ECG entity, or a mosaic in the palette of acute coronary syndromes. The author presents three different ECG manifestations of the Dressler–de Winter sign. The Dressler–de Winter sign and STEMI not only show temporal dynamicity, but the two ECG patterns can coexist in the same electrocardiograms. This observation strongly argues for a true ischemic etiology rather than being due to anatomical variations of the Purkinje fibers or lack of activation of sarcolemmal ATP-sensitive potassium (KATP) channels by ischemic ATP depletion, as was originally proposed.